Communicative Construction of Native versus Non-Native Swedish Speaking Patients in Consultation Settings - Hedegaard, Joel; Rovio-Johansson, Airi; Siouta, Eleni (Scandinavian Journal of Public Administration, 2013)
In this paper, we examine patient-centered care through analyzing communicative constructions of patients, on the basis of their native language, in consultations with physicians. Whereas patient-centered care is of current interest in health care, research has not addressed its implications in this dimension. Previous studies indicate that non-native Swedish speaking patients, experience substandard interpersonal treatment far more than native Swedish speaking patients. Our findings show that the non-native Swedish speaking patients presented themselves as participating, whereas the native Swedish speaking patients presented themselves as amenable. The physicians responded in two different ways, argumentatively towards the non-native Swedish speaking patients and acknowl- edging vis-à-vis the native Swedish speaking patients. When decisions and conclusions were made by the patients and physicians, this resulted in preservation of the status quo in the consultations with the non-native Swedish speaking patients, while the corresponding result with the native Swedish speaking patients was monitoring of their health status. So, whereas the non-native Swedish speaking patients actually were model patient-centered care patients, physicians were more amenable towards the native Swedish speaking patients. We suggest that patient-centered care is desirable, but its practical application must be more thoroughly scrutinized from both a patient and a health care worker perspective.